2012
DOI: 10.1002/ceat.201100586
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Conjugated Heat Transfer in Direct‐Contact Membrane Distillation of Seawater Desalination Systems

Abstract: The modeling equations for the temperature distribution and temperature polarization profiles in a laminar concurrent‐flow parallel‐plate direct‐contact membrane distillation (DCMD) module were developed theoretically. The analytical solutions for such conjugated Graetz problems in DCMD systems were obtained using the variable separation method with an orthogonal expansion technique extended in power series. A description of the average Nusselt number variations and temperature distributions of both the hot an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The applicability, validity, and robustness of the FEM for the type of domain encountered in the present work have been demonstrated previously by a number of authors [15][16][17][18][19][20][21]. A grid independence test indicated that the optimum numbers of meshes were 10 064 for numerical simulation [22][23][24][25]. Tab.…”
Section: Numerical Solution Of Model Equationssupporting
confidence: 65%
“…The applicability, validity, and robustness of the FEM for the type of domain encountered in the present work have been demonstrated previously by a number of authors [15][16][17][18][19][20][21]. A grid independence test indicated that the optimum numbers of meshes were 10 064 for numerical simulation [22][23][24][25]. Tab.…”
Section: Numerical Solution Of Model Equationssupporting
confidence: 65%
“…Because it is in equilibrium with the liquid phase, a lower temperature on the feed side causes the partial vapor pressure to decrease, while a higher temperature on the permeate side causes the partial pressure to increase. The authors in [40] reported that the effect of initial saline temperature on the hot feed stream regarding pure water productivity is more significant than that of the hot and cold feed stream velocity variations.…”
Section: Effect Of Pulsating On the Temperature Polarization Of Bulk ...mentioning
confidence: 99%
“…Temperature polarization is one of the key problems with the MD membrane, and when it comes to the bundle of hollow fibers on the MD membrane, it is quite challenging to calculate precise temperature polarization. Many scientists have predicted temperature polarization, maybe in light of the experimental study in [40] where a series of electrical sensors were used to predict the experimental and theoretical temperature polarization of DCMD. Besides that, the majority of them demonstrated that the bulk feed and permeate solutions' temperatures (T f and T p ) varied from one another [24,41].…”
Section: Effect Of Pulsating On the Temperature Polarization Of Bulk ...mentioning
confidence: 99%
“…By combining Eqs. (1), (5)-(8) and rearranging, the following expressions for T mf and T mp can be obtained (Bouguecha et al 2003;Ho et al 2012):…”
Section: Modelling the Mass And Heat Transfer Phenomena In Dcmdmentioning
confidence: 99%